Compromiso del sistema nervioso central en la enfermedad de Carrión - Maguiña, C.; Acosta, V.R.; Gotuzzo, E.; Cabrera, J.; Campos, P.; Echevarria, J.; Vizcarra, D.; Cok, J.; Ferrufino, J. (Revista de Neuro-Psiquiatría, 2013)
.